Communication Styles During Teaching Learning Process in EFL Classroom - Muhammad Fauzi Romadhon Marpaung; Raden Sri Ayu Ramadhana (Departement of Mathematics Education, 2024)
This research was aimed to analyze communication styles during teaching learning process in classroom. The research was conducted by using qualitative descriptive design. The data of this study were the utterances of teaching learning process in a classroom which is a conversation classroom in an English Institution Course, which was transcribed into the written form. The conclusion that can be drawn is that all of the types of communication styles basically occurred in the teaching and learning process. The types of physical communication styles are aggressive, passive, passive – aggressive, and assertive. In the teaching and learning process, assertive communication styles was the dominant communication style happening in the process for 67%, followed by Passive as 16%, passive – aggressive 12%, and aggressive 5%. It showed that the assertive communication style is the dominant style that is used in teaching and learning process as this style is the good style to comfort people while communicating each other. So, to convey message especially in teaching learning process, it is needed an effective communication to achieve the nature of the learning itself.